A re-assessment of Hexapleomera Dudich, 1931 (Crustacea: Tanaidacea: Tanaidae), with designation of three new species - Bamber, Roger N. (Zootaxa, 2012)
The tanaid genus Hexapleomera has long been considered to be monotypic, comprising a cosmopolitan species predom-inantly commensal on turtles, or, more rarely, manatees. Recent discovery of material of a distinct species ofHexapleomera living on the hulls of yachts in south-west England encouraged re-assessment of the literature on this taxon,and re-examination of free-living benthic material from the eastern Mediterranean. As a result, five species are recognizedwithin the genus Hexapleomera; two new species are described, Pancoloides moverlyi is moved to Hexapleomera, and H. robusta sensu Edgar is elevated to specific rank and re-named.